1990
DOI: 10.1111/j.1365-2141.1990.tb04347.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic, immunologic and cytogenetic studies in erythroleukaemia: evidence for multilineage involvement and identification of two distinct cytogenetic‐clihicopathological types

Abstract: Clinical features, as well as morphology, immunophenotype and cytogenetics were retrospectively studied in 20 patients with an original diagnosis of erythroleukaemia (EL) reclassified according to the FAB criteria. Fifteen patients had de novo EL, five patients had therapy-related EL. Myelodysplasia preceded the onset of EL in eight cases and myelodysplastic features involving multiple haemopoietic lineages were observed at leukaemia presentation in all cases. Immunologic findings confirmed multilineage involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0
5

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 35 publications
6
23
0
5
Order By: Relevance
“…This is consistent with previous studies in which no specific pattern was found. In our series, involvement of chromosomes 5 or 7 was observed in 6 patients; these abnormalities were also found in other series of patients with EL 9,15,26,30,41 and were associated with poor prognosis. 15 Trisomy 8 was observed in 6 patients and reported in previous series of patients with EL.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with previous studies in which no specific pattern was found. In our series, involvement of chromosomes 5 or 7 was observed in 6 patients; these abnormalities were also found in other series of patients with EL 9,15,26,30,41 and were associated with poor prognosis. 15 Trisomy 8 was observed in 6 patients and reported in previous series of patients with EL.…”
Section: Discussionsupporting
confidence: 87%
“…15 Trisomy 8 was observed in 6 patients and reported in previous series of patients with EL. 9,15,30 These abnormalities on chromosomes 5, 7, and 8 are also described in MDS. 42 We conclude that patients with EL who achieve CR1 should proceed to HLA matched allogeneic HSCT if a family donor is available.…”
Section: Discussionmentioning
confidence: 89%
“…However, for other authors, more than the percentage of erythroblasts, cytogenetic abnormalities correlate with the rate of CR. 12,17,21,22 Age is an important factor; older patients have a low CR and a short survival. Expression of P-glycoprotein is clearly a poor factor of survival.…”
Section: Prognosismentioning
confidence: 99%
“…The percentage of pronormoblast seems an important factor of survival according to Kowal-Vern et al [16] with a mean survival of 34 months in AML6a, 3.5 months in AML6b and 10.5 months for AML6c. However, for other authors, more than the percentage of erythroblasts, cytogenetic abnormalities correlate with the rate of CR [13,[17][18][19]. Age is an important factor; older patients have a low CR and a short survival.…”
Section: Prognosismentioning
confidence: 97%